The Role of Qi-Stagnation Constitution and Emotion Regulation in the Association Between Childhood Maltreatment and Depression in Chinese College Students - Huang, Huiyuan; Song, Quanwu; Chen, Jiawen; Zeng, Ying; Wang, Wenqi; Jiao, Bingqing; Lin, Jiabao; Li, Yan; Zhang, Rong; Ma, Lijun; Pan, Huafeng; Shi, Yafei (Frontiers in Psychiatry, 2022)
Background: Childhood maltreatment is known as a significant risk factor for later depression. However, there remains a lack of understanding about the mechanisms through which childhood maltreatment confers risk for depression. This study explores how Qi-stagnation constitution (QSC) and emotion regulation affect the link between childhood maltreatment and depressive symptoms in Chinese college students. Methods: We recruited 2108 college students aged 18-25 years between November 2020 and December 2021. Participants were required to complete four self-report questionnaires, including the Childhood Trauma Questionnaire-Short Form (CTQ-SF), Qi-Stagnation Constitution (QSC) subscale of the simplified Chinese Medicine Constitution Questionnaire, Difficulties in Emotion Regulation Scale (DERS) and the Beck Depression Inventory-II (BDI-II). Moderated mediation analyses were conducted. Results: There was a positive correlation between childhood maltreatment and QSC, while the QSC partially mediated the effect of childhood maltreatment on depressive scores in college students. In addition, emotion dysregulation moderated the association between QSC and depressive scores. Conclusions: These results enhance understanding of key factors influencing the link between childhood maltreatment and depressive symptoms among college students by combining the theory of TCM constitution with psychological processes. The development of strategies to prevent biased Qi-stagnation constitution and emotion dysregulation may help to improve college students’ mental health and strengthen the resilience of individuals to depression.